Looking through darkness a Trading Post novel - Thurlo, Aimee; Thurlo, David (New York Forge, 2015)
"Few writers have captured the flavor of the American Southwest better than Aimee and David Thurlo, in both mysteries and romantic suspense. Josephine Buck runs a trading post just off the Navajo Reservation. Widow Leigh Ann Vance is Jo's right-hand-woman, filling the emptiness in her own life. Shortly after her husband, Kurt, was killed, Leigh Ann discovered he had been having a string of affairs. Leigh Ann's trust issues affect her feelings for blind sculptor Melvin Littlewater. Kurt's business partners accuse Leigh Ann of helping Kurt embezzle and the police wonder if Leigh Ann killed him. When she turns to Melvin for help, she finds him fighting his own demons, haunted by memories of a young girl he saw moments before the car crash that cost him his sight. Together, Leigh Ann and Melvin delve into the darkest moments of their pasts, searching for truth and light"--
"A Trading Post novel"--Jacket.
Keywords: Widows; Man-woman relationships; Fiction / Romance / Suspense; Fiction / Mystery & Detective / Women Sleuths; Mystery fiction; Romantic suspense fiction